Meningkatkan Hasil Belajar IPA Dengan Metode Eksperimen - Gemala Widiyarti (JURNAL TARBIYAH, 2018)
This research is a Classroom Action Research (CAR) experimental method on science subjects. The research problem in this research is the students’ low score in learning natural sciences. This study aims to determine the implementation of learning and student learning outcomes. From the data analysis, obtained by teacher observation with percentage 78,2% and student activity 74% which included in good category. Completeness of learning outcomes in the first cycle there are 18 students who complete the study with a percentage of 75%, while in the second cycle increased to 21 students who complete learning with percentage 87.5%, and the average value also increased from 67.75 to 75 , 41.